Primary Endocrine Therapy for Locally Advanced Breast Cancer—Is it an Inferior Approach? Experience from Nottingham - Lakshmanan, Radhika (Springer-Verlag, 2010)
Treatment strategy for locally advanced primary breast cancer(LAPC) remains mainly multimodal involving neoadjuvant chemotherapy, surgery followed by radiotherapy and endocrine therapy, all given upfront. There have been few studies comparing this with a sequential treatment approach, for instance, using endocrine therapy as initial treatment. Based on small randomised clinical trials and local experience in Nottingham, primary endocrine therapy has been shown to produce very good early (response) and late (survival) outcome when used in ER positive, noninflammatory LAPC. This could be considered as a viable therapeutic option in appropriately selected patients.